A cubic dual band near‐field focused array antenna using composite right/left handed transmission lines. Issue 1 (19th October 2021) - Kamyab, Omid Reza; Jam, Shahrokh
Abstract: This paper proposes a new method for design of a dual‐frequency near field‐focused (NFF) antenna. A 4 × 4 array of dual‐band patches and a dual‐band feed network are designed to provide a phase distribution at 2.4 and 5.8 GHz. Rectangular patches with U‐shaped slot be used as the double‐band patches. The composite right/left handed transmission lines (CRLH TL) are used in design of a dual‐band phase distribution network for the patches. Finally, a three‐dimensional cubic structure is proposed to isolate the feed network and thereby improve the antenna performance. A prototype of a cubic dual band 4 × 4 near field focused array antenna is fabricated and tested. The measurement results have good agreement with simulation results.